Sunscreens: UV filters to protect us: Part 2-Increasing awareness of UV filters and their potential toxicities to us and our environment - David Fivenson, MD; Nina Sabzevari, DO; Sultan Qiblawi, MBA, M3; Jason Blitz, MD, MPH; Benjamin B. Norton, MD, MPH&TM; Scott A. Norton, MD, MPH, MSc (Wolters Kluwer, 2021)
Background: Sunscreens are topical preparations containing one or more compounds that filter, block, reflect, scatter, or absorb ultraviolet (UV) light. Part 2 of this review focuses on the environmental, ecological effects and human toxicities that have been attributed to UV filters. Methods: Literature review using NIH databases (eg, PubMed and Medline), FDA and EPA databases, Google Scholar, the Federal Register, and the Code of Federal Regulations (CFR). Limitations: This was a retrospective literature review that involved many different types of studies across a variety of species. Comparison between reports is limited by variations in methodology and criteria for toxicity. Conclusions: In vivo and in vitro studies on the environmental and biological effects of UV filters show a wide array of unanticipated adverse effects on the environment and exposed organisms. Coral bleaching receives considerable attention from the lay press, but the scientific literature identifies potential toxicities of endocrine, neurologic, neoplastic and developmental pathways. These effects harm a vast array of aquatic and marine biota, while almost no data supports human toxicity at currently used quantities (with the exception of contact allergy). Much of these data are from experimental studies or field observations; more controlled environmental studies and long-term human use data are limited. Several jurisdictions have prohibited specific UV filters, but this does not adequately address the dichotomy of the benefits of photoprotection vs lack of eco-friendly, safe, and FDA-approved alternatives.